2007
DOI: 10.1111/j.1365-2427.2007.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria–algae association in batch cultures of phytoplankton from a tropical reservoir: the significance of algal carbohydrates

Abstract: 1. The dissolved organic matter, especially carbohydrates, released by phytoplanktonic organisms may be ecologically important, through its influence on carbon cycling and microbial diversity. Here axenic cultures of three phytoplanktonic species, Cryptomonas tetrapyrenoidosa (Cryptophyceae), Staurastrum orbiculare (Zygnematophyceae) and Thalassiosira duostra (Bacillariophyceae), were inoculated with a microbial community from the same habitat in which the algae had been isolated (a tropical reservoir). Replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…However, bacteria populations increased when, or soon after, the phytoplankton biomass reached it maximum. Giroldo, Ortoland & Vieira (2007) also found that phytoplanktonic extracellular organic compounds, including carbohydrates, supported dense bacterial populations, even at very low concentrations. Dissolved EPS released from phytoplankton is a major component of dissolved organic carbon (DOC) in freshwater and is beneficial for bacterial growth (Sundh, 1992).…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
“…However, bacteria populations increased when, or soon after, the phytoplankton biomass reached it maximum. Giroldo, Ortoland & Vieira (2007) also found that phytoplanktonic extracellular organic compounds, including carbohydrates, supported dense bacterial populations, even at very low concentrations. Dissolved EPS released from phytoplankton is a major component of dissolved organic carbon (DOC) in freshwater and is beneficial for bacterial growth (Sundh, 1992).…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
“…Sundh 1992, Giroldo et al 2007). Even so, it is not known which algal species are the major EPP producers, though tight species-specific algal-bacterial relationships have been suggested for naturally occurring bacterial-algal consortia (Lindström 2001, Grossart et al 2005, Murray et al 2007.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Although the high availability of phytoplankton-originated DOC it can still be accumulated during blooms of freshwater phytoplankton, creating a pool of residual DOC (Kragh and Søndergaard, 2004). Different compounds, like polysaccharides, might be more or less degradable by bacteria (Giroldo et al, 2007), requiring specific adaptations for its success and even the degradation itself might result in more refractory compounds (Bittar et al, 2015). However, this residual DOC still have a appreciable return to the pelagic food web via bacterial consumption (Coveney and Wetzel, 1989), although at a slower pace, and thus, assuming an considerable ecological role.…”
Section: Degradation Kinetics Of Dissolved Organic Carbon and Nitrogenmentioning
confidence: 99%
“…The quality and availability of compounds in these released DOM and the presence of specialists and generalists bacterial groups will influence the bacterial community composition during the degradation process (Allen et al, 2005;Davidson et al, 2007;Giroldo et al, 2007). Therefore, we focused on trying to estimate the fate of dissolved organic carbon and nitrogen released by axenic cultures of P. agardhii under bacterial degradation, and simultaneously determine the main bacterial OTUs (Operational taxonomic units) involved in the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation